INTEGRASI CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN ZAKAT MAAL PADA PERUSAHAAN - Firmansyah, Kholis (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2020)
Companies in Indonesia are responsible for contributing to the state and society, including providing Corporate Social Responsibility (CSR) funds according to the constitution UU No.40 Tahun 2007, pay taxes according to the constitution UU No.36 tahun 2008 and pay zakat according to the constitution UU No.23 Tahun 2011 (for Muslim-owned companies). so, the company has three obligations, namely : issuing CSR, paying taxes and zakat. In this case the author will examine how the implementation of PT. Telekomunikasi Indonesia, Tbk. in integrating the obligation to channel CSR funds with Zakat Maal. This research is a qualitative research, with an exploration method, and is descriptive in nature. Methods of data collection by means of observation, interview, focus group discussion and documentation. And the data analysis method used in this research is descriptive analysis method. The result of this research is PT. Telekomunikasi Indonesia, Tbk. Witel Sidoarjo integrates the obligation to issue Corporate Social Responsibility (CSR) funds and Zakat Maal by calculating: 3% x (Current Assets - Accounts Payable). Then from the 3%, 2% is allocated in the CSR program and 1% is allocated in the Zakat Maal program. Then distributed to the community with partnership, education, health, social and religious programs.